W(CO)5(L)-Catalyzed Cyclization of α-Alkynyl-β-dicarbonyl Derivatives: Synthesis of Methylenelactones, Furans, and Methylenecyclopentanes - Meng, Xiangjian; Kim, Sunggak (Synlett, 2012)
W(CO)5(L)-Catalyzed cyclization of α-alkynyl-β-keto acids, keto esters, and diketones provides methylenelactones, furans, and methylenecyclopentanes via 5-exo-dig cyclization. Also, the present approach can be further applied to 5-endo-dig cyclization.
Keywords: tungsten; cyclization; methylenelactones; furans; methylenecyclopentanes